Menggugah Partisipasi & Membangun Sinergi: Upaya Bergerak dari Stagnasi Ekologis Pengelolaan Sampah - Lailiy Muthmainnah (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2007)
Current approach of the government on managing waste is still focused on localizing waste by implementing method of TPA (Final Disposal Site), in which waste materials are collected and disposed in a certain area. This approachhas receiaed wide criticisms since it failed to anticipate the ecological and environmental degradation. This paper argues that the approach in waste management should not only focused on the 'end of pipe' method but also increasing the effort of 'clean production' mechanism. Using the case of waste management in Yogyakarta, this paper suggests some steps to synergizing the approaches and highlights the important of stakeholders' participation in optimizing waste management while preserving the environment.